2013
DOI: 10.1177/0956797613481233
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable Neural Routes to Successful Prospective Memory

Abstract: Identifying the processes by which people remember to execute an intention at an appropriate moment (prospective memory) remains a fundamental theoretical challenge. One account is that top-down attentional control is required to maintain activation of the intention, self-initiate intention retrieval, or support monitoring. A diverging account suggests bottom-up spontaneous retrieval can be triggered by cues that have been associated with the intention; sustained attentional processes are not required. We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
122
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(147 citation statements)
references
References 36 publications
(66 reference statements)
18
122
5
Order By: Relevance
“…His findings were later reproduced in other studies [6] [7]. Several fMRI studies also link prefrontal lobe activity directly to PM task performance, and shown that each time participants respond appropriately to a PM cue, the cognitive processing resources would reallocation [8] [9] [10]. As a result, for the current study, we aim to further investigate this relationship in an immersive virtual reality environment.…”
Section: Introductionsupporting
confidence: 55%
“…His findings were later reproduced in other studies [6] [7]. Several fMRI studies also link prefrontal lobe activity directly to PM task performance, and shown that each time participants respond appropriately to a PM cue, the cognitive processing resources would reallocation [8] [9] [10]. As a result, for the current study, we aim to further investigate this relationship in an immersive virtual reality environment.…”
Section: Introductionsupporting
confidence: 55%
“…Prefrontal regions, including the rostral prefrontal cortex (BA10), consistently activate during PM performance in healthy individuals potentially reflecting intention maintenance [17,18]. Lesions to prefrontal regions have been shown to significantly compromise PM function [19,20], corroborating the neuroimaging findings.…”
Section: Introductionmentioning
confidence: 55%
“…In addition, in an aging study, age-related differences in PM were mediated by processing speed, inhibitory control, and working memory (West & Craik, 2001). Finally, several studies using functional neuroimaging and event-related potentials have indicated the important role of various regions in the prefrontal and parietal cortices in prospective memory processes suggesting that working memory, inhibition, and attention switching between external events and internal thought processes are likely operating during prospective remembering (Bisiacchi, Schiff, Ciccola, & Kliegel, 2009;Burgess, Quayle, & Frith, 2001;Czernochowski, Horn, & Bayen, 2012;Martin et al, 2007;Mattli, Zöllig, & West, 2011;McDaniel et al, 1999;McDaniel, LaMontagne, Beck, Scullin, & Braver, 2013;Okuda et al, 1998;Simons, Schölvinck, Gilbert, Frith, & Burgess, 2006;West, 2011;West & Covell, 2001;Zöllig et al, 2007).…”
Section: Executive Function and Prospective Memory In Adulthoodmentioning
confidence: 97%